2014
DOI: 10.1044/vvd24.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Using Semi-Occluded Vocal Tract Exercises in Voice Therapy: The Clinician's Primer

Abstract: Semi-occluded vocal tract (SOVT) exercises have long been used by voice trainers and pedagogues and have been particularly popular in Scandinavia dating as far back as the 1800s. Titze (1988, 1994, 2006; Titze, Riede, & Popolo, 2008; Titze & Verdolini-Abbot, 2012) has contributed significantly to the exploration of the SOVT and impact on voice production, and these types of exercise have become ubiquitous in the clinical voice arena. Although SOVT exercises are commonly used, there continue to be quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“… Clinicians should avoid exercises that trigger cough or excess droplets such as tongue and lip vibrations. Optional exercises, such as hand-over-mouth, 104 cup phonation technique, 105 or the semi-occluded face mask, may be good alternatives to avoid the spreading of particles. Clinicians must provide vocal hygiene habits to patients.…”
Section: Early Approach After Invasive Mechanical Ventilationmentioning
confidence: 99%
“… Clinicians should avoid exercises that trigger cough or excess droplets such as tongue and lip vibrations. Optional exercises, such as hand-over-mouth, 104 cup phonation technique, 105 or the semi-occluded face mask, may be good alternatives to avoid the spreading of particles. Clinicians must provide vocal hygiene habits to patients.…”
Section: Early Approach After Invasive Mechanical Ventilationmentioning
confidence: 99%
“…8, 12 Although there is limited research regarding the effectiveness of SOFM therapies, early studies have shown promise. 18, 19, 20 For example, Fouquet et al used a hands-over-mouth technique to evaluate vocal quality and found that this semi-occlusion strategy could be used to promote vocal fold adduction and reduce phonatory effort. 19 Also, Rosenberg used a cup phonation method, in which a small occlusion was made at the bottom of a cup, which allowed for continuous phonation tasks to be performed through the open side.…”
Section: Introductionmentioning
confidence: 99%
“…19 Also, Rosenberg used a cup phonation method, in which a small occlusion was made at the bottom of a cup, which allowed for continuous phonation tasks to be performed through the open side. 20 Although these studies are promising, these methods did not allow for the simple attachment of various resonance tubes and also for the addition of oppositional airflow.…”
Section: Introductionmentioning
confidence: 99%
“…O clínico deverá ser sempre cuidadoso para que não cause qualquer trauma adicional ou hiperfunção mal adaptativa. Deve-se evitar exercícios que estimulem tosse ou excesso de gotículas como a vibração de lábios; alternativas como a técnica de firmeza glótica ( hand-over-mouth ), 104 fonação em copos, 105 ou máscaras de resistência, podem ser boas opções para evitar que as partículas se espalhem. Explicar e incentivar hábitos adequados para a saúde vocal dos pacientes.…”
Section: Abordagem Inicial Após Ventilação Mecânica Invasivaunclassified